An epidemiological study of anaemia in the women of reproductive age group (15-49 years) residing in field practice area of a medical college, Udaipur (Rajasthan) - Solanki, Shiv Lal; Coudhary, Bhagraj; Vishnoi, Bhagwan Ram; Vyas, B. L. (International Journal Of Community Medicine And Public Health, 2017)
Background: Anaemia is one of the most important public health problem that persist worldwide, affecting the infants, young children, adolescents, elderly and child bearing women of developing countries. Among the women of reproductive age group the adolescence period is crucial and dynamic for young females as they begin to develop their capacity for empathy, abstract thinking for physical and mental induration with future time perspective of growth and development. The objectives of the study were to assess the prevalence of anaemia in women of reproductive age group; to study the socio-demographic factors among the study subjects Methods: A cross- sectional purposive study was conducted on 436 females of reproductive age group, residing in the field practice area of urban health training centre of department of community medicine, Geetanjali medical college and hospital, Udaipur. Study period was from May 2015 to April 2016. Results: The prevalence of anaemia among the age group below 18 years were (71.2%), educated (72.4%), nuclear family (73.3%), married (87.1%), socio-economic status group V (79.9%), menarche (75.15%), and severe anaemia was observed in (3.2%) subjects. Conclusions: Nutritional anaemia is one of the most common micronutrient deficiency observed in the world and is the highest in the adolescent females. The study revealed the statistically significant association of anaemia with various socio-demographic factors.